Pengaruh Persepsi Kegunaan dan Persepsi Kemudahan terhadap Penerimaan Pengguna Aplikasi Myunnes sebagai Layanan Digital Kampus Universitas Negeri Semarang Menggunakan Technology Acceptance Model (TAM) - Desi Samin; Fahrur Rozi (INSOLOGI: Jurnal Sains dan Teknologi, 2026)
The expansion of digital technologies in higher education has encouraged universities to modernize academic services through digital applications, one of which is MyUNNES, the academic service platform developed by Universitas Negeri Semarang. Drawing upon Technology Acceptance Model (TAM), this research investigates whether perceived usefulness (PU) and perceived ease of use (PEOU) contribute to users' acceptance of MyUNNES application. In this context, success of platform is evaluated not merely by its functional capabilities but by degree to which it is accepted by its users. A quantitative methodology with a causal research design was employed. The study collected data by administering questionnaires to 393 active students of Universitas Negeri Semarang who had previously used MyUNNES application. The respondents were recruited through purposive sampling, and resulting data were processed using multiple linear regression analysis. The statistical results demonstrate PU together with PEOU has a positive and significantly influence on user acceptance, as reflected by an F-value of 391.970 (p < α). The findings further indicate students are more likely to accept MyUNNES application when they perceive it as both beneficial and effortless to operate. These results are consistent with TAM, which emphasizes PU and PEOU are principal factors driving acceptance of digital technologies in higher education.